Personality-augmented MPC: Linking survey and transaction data to explain MPC heterogeneity by Big Five personality traits - Fabian Nemeczek; Jan Radermacher (Leibniz Institute for Financial Research SAFE, 2022)
We investigate the link between Big Five personality traits and the marginal propensity to consume (MPC) for users of a German financial account aggregator app. We use 1,700 survey responses and transaction data of 56,000 app users to assess whether Big Five personality traits help explain MPC heterogeneity. We find that extraversion corresponds to an increase in consumption whereas agreeableness and neuroticism correspond to a decrease in consumption. We test this with trust and risk preferences and find that risk indicates more explanatory power in consumption response than the Big Five. Our findings help policy makers target individuals more efficiently.
Keywords: 330; Marginal Propensity to Consume; Big Five Personality; Survey Data; Transaction Data